Direct Evidence of Active and Rapid Nuclear Degradation Triggered by Vacuole Rupture during Programmed Cell Death in Zinnia - Obara, Keisuke (American Society of Plant Physiologists, 2001)
Differentiation into a tracheary element (TE) is a typical example of programmed cell death (PCD) in the developmental processes of vascular plants. In the PCD process the TE degrades its cellular contents and becomes a hollow corpse that serves as a water conduct. Using a zinnia (Zinnia elegans) cell culture we obtained serial observations of single living cells undergoing TE PCD by confocal laser scanning microscopy. Vital staining was performed and the relative fluorescence intensity was measured, revealing that the tonoplast of the swollen vacuole in TEs loses selective permeability of fluorescein just before its physical rupture. After the vacuole ruptured the nucleus was degraded rapidly within 10 to 20 min. No prominent chromatin condensation or nuclear fragmentation occurred in this process. Nucleoids in chloroplasts were also degraded in a similar time course to that of the nucleus. Degradations did not occur in non-TEs forced to rupture the vacuole by probenecid treatment. These results demonstrate that TE differentiation involves a unique type of PCD in which active and rapid nuclear degradation is triggered by vacuole rupture.